Simulating Cluster Formation and Radiative Feedback in Molecular Clouds - Howard, Corey S. (My University, 2013)
The formation of star clusters occurs in a complex environment and involve a large number of physical processes. One of the most important processes to consider is radiative feedback. The radiation released by forming stars heats the surrounding gas and suppresses the fragmentation of low mass objects. Ionizing radiation can also drive large scale outflows and disperse the surrounding gas. Owing to all this complexity, the use of numerical simulations to study cluster formation in molecular clouds has become commonplace. In order to study the effects of radiative feedback on cluster formation over larger spatial scales than previous studies, we present hydrodynamical simulations using the AMR code FLASH which make use of cluster particles. Unlike previous studies, these particles represent an entire star cluster rather than individual stars. We present a subgrid model for representing the radiative output of a star cluster which involves randomly sampling an IMF over time to populate the cluster. We show that our model is capable of reproducing the properties of observed clusters. The model was then incorporated into FLASH to examine the effects of radiative feedback on cluster formation in full hydrodynamical simulations. We find that the inclusion of radiative transfer can drive large scale outflows and decreases the overall star formation efficiency by a factor of 2. The inclusion of radiative feedback also increases the degree of subclustering. The use of cluster particles in hydrodynamical simulations represents a promising method for future studies of cluster formation and the large scale effects of radiative feedback.
Keywords: Star clusters; Star formation; Numerical simulations; Radiative feedback; Molecular clouds; Stars, Interstellar Medium and the Galaxy; Stars, Interstellar Medium and the Galaxy